Identification of Mutation Landscape and Immune Cell Component for Liver Hepatocellular Carcinoma Highlights Potential Therapeutic Targets and Prognostic Markers - Wang, Hengzhen; Jiang, Wenjing; Wang, Haijun; Wei, Zheng; Li, Hali; Yan, Haichao; Han, Peng (Frontiers in Genetics, 2021)
Liver hepatocellular carcinoma (LIHC) is a primary malignancy and there is a lack of effective treatment for advanced patients. Although numerous studies exist to reveal the carcinogenic mechanism of LIHC, few studies have integrated multi-omics data to systematically analyze pathogenesis and reveal potential therapeutic targets. Here, we integrated genomic variation data and RNA-seq profiles obtained by high-throughput sequencing to define High- and Low-genomic instability samples. The mutational landscape was reported and the advanced patients of LIHC were characterized by high genomic instability. We found that the tumor microenvironment undergoes metabolic reprograming drove by mutations accumulate to satisfy tumor proliferation and invasion. Further, the co-expression network identifies three mutant lncRNAs as potential therapeutic targets, which can promote tumor progression by participating in specific carcinogenic mechanisms. Then, five prognostic markers were identified by examining the association of genes and patient survival. By characterizing the immune landscape of LIHC, loss of immunogenicity was revealed as a key factor of immune checkpoint suppression. Macrophages were found to be significantly associated with patient risk scores and high levels of macrophages accelerated patient mortality. In summary, the mutation-driven mechanism and immune landscape of LIHC revealed by this study will serve precision medicine.